THE EFFECT OF COMIC MEDIA IN PHYSICH LEARNING TOWARD STUDENT’S CONCEPT MASTERY - Salam, Abdul; Hidayat, Samsun; Ahzan, Sukainil (IKIP Mataram, 2016)
This research aims to determine the effect comics Media the mastery toward concepts of Physics Students Class VIII MTs NW Sanggeng the Academic Year 2015/2016. Research type used is experimental research. The population in this study is all students of class VIII MTs NW Sanggeng. Samples used is class VIIIA totaling 21 people as a class experiment and VIIIB students of 20 people as the control class taken with purposive sampling technique. The data in this study taken to give the initial test and final test to students sample. Data collection techniques using test questions Essay. Based on the analysis of data obtained by the average value of the initial test of the experimental class 13.29 and the control class is 12.85. Final test results showed an average grade of 63.05 experiment and the control class 49.10. Data final test graders samples were analyzed using t-test. Based on the results of data analysis using t-test obtained tcalculate equal to 2,756 and ttable of 2.002. Obtained thitung greater than t table at a 5% error level, so Ha is received, it can be concluded that there is effect from the use Media comic the mastery toward concepts of Physics Students Class VIII MTs NW Sanggeng in the academic year 2015/2016.